UT system : a structural system to build taller urban timber houses with aspired spatial flexibility - Silva, Catarina V. (2014)
In past few years, in consequence to the continuous increase of urban densities and seeking for a more sustainable profile for construction, some new proposals for tall timber city housing have emerged. The development of new wood-based materials, like cross laminated timber (CLT), has made possible to believe to build high with timber. Demonstration buildings located in different locations around the world contribute to the development of this new concept of urban housing. With the exception of few recent proposals based on hybrid systems, majority of buildings so far built are fully based in the monolithic construction system offered by CLT panels. Despite all the advantages related with this monolithic system, two main important weaknesses related with architectural freedom have been pointed out: the excessive compartmentalization of inner spaces and the external expression of an extruded box with reduced openings. Inspired on new CLT/steel and CLT/concrete hybrid proposals and their advantages in comparison to the CLT monolithic system, a CLT/glulam hybrid construction system, named UT system (urban timber system), has been developed. CLT remains the main structural material in the UT system but, glulam linear elements are used to reduce the CLT walls both inside and in the building perimeter. Further, based in the bundled tube concept, UT system looks into the possibility of overcome eccentricity problems caused by non-symmetrical location of vertical cores and consequently, offers more design freedom. UT system is described and illustrated, considering concerns related with structural system, tall building specificities, construction sequences, architectural design possibilities, moisture effects, durability, fire resistance, acoustic performance and joints between timber elements.